2007
DOI: 10.1155/2007/56165
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) and Palladium(II) Complexes of Pyridine-2-Carbaldehyde Thiosemicarbazone as Alternative Antiherpes Simplex Virus Agents

Abstract: The cytotoxicity and the antivirus activity of Pd(II) and Pt(II) complexes with pyridine-2-carbaldehyde thiosemicarbazone (HFoTsc) against HSV replication were evaluated on four HSV strains—two wt strains Victoria (HSV-1) and BJA (HSV-2) and two ACVR mutants with different tk gene mutations R-100 (TKA, HSV-1) and PU (TKN, HSV-2). The experiments were performed on continuous MDBK cells and four HSV 1 and HSV 2 strains were used, two sensitive to acyclovir and two resistant mutants. The five complexes of HFoTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…The synthesis of transition metal complexes with thiosemicarbazone ligands have been receiving considerable attention due to the pharmacological properties of both ligands and complexes [1][2][3] .The Chemistry of Thiosemicarbazone has received considerable attention because of their variable bonding modes, promising biological implications, structural diversity, and ion -sensing ability [4][5][6] .The ligand, based on semicarbazone and pyridoxal moieties(forms found in vitamin B6), has an enormous potential as a biologically active reagent as it has been demonstrated that transition metal complexes incorporating semicarbazones show biological activity. In particular, with regard to biological importance, nickel(II) complexes with semicarbazone ligands show antibacterial acivity 7 , and copper(II) complexes containing semicarbazones have also displayed biological properties [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of transition metal complexes with thiosemicarbazone ligands have been receiving considerable attention due to the pharmacological properties of both ligands and complexes [1][2][3] .The Chemistry of Thiosemicarbazone has received considerable attention because of their variable bonding modes, promising biological implications, structural diversity, and ion -sensing ability [4][5][6] .The ligand, based on semicarbazone and pyridoxal moieties(forms found in vitamin B6), has an enormous potential as a biologically active reagent as it has been demonstrated that transition metal complexes incorporating semicarbazones show biological activity. In particular, with regard to biological importance, nickel(II) complexes with semicarbazone ligands show antibacterial acivity 7 , and copper(II) complexes containing semicarbazones have also displayed biological properties [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2005); cell refinement: APEX2 ; data reduction: SAINT (Bruker, 2005); program(s) used to solve structure: SHELXTL (Sheldrick, 2008); program(s) used to refine structure: SHELXTL; molecular graphics: SHELXTL; software used to prepare material for publication: SHELXTL and PLATON (Spek, 2003 The chemistry of thiosemicarbazones have been of immense interest because these compounds provide intriguing chelating patterns, profound biomedical properties, structural diversity and ion-sensing abilities (Al-Awadi et al, 2008;Amoedo et al, 2006;Demertzi et al, 2007;Mirsha et al, 2006;Kizilcikli et al, 2004). Compounds of this type have been used as antibacterial, antifungal and antitumor agents (Sing et al, 2001;Offiong et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…For related structures of thiosemicarbazones, see, for example: John et al (2003); Joseph et al (2004). For applications and bioactivities of thiosemicarbazones, see, for example: Al-Awadi et al (2008); Amoedo et al (2006); Chandra et al, (2001); Demertzi et al (2007); Kizilcikli et al (2004); Mirsha et al (2006); Offiong & Martelli (1997); Sing et al (2001). Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Thiosemicarbazones are metal chelators and their derivatives quench reactive oxygen species . Copperbis(thiosemicarbazonato) complexes are found to reduce levels of Aβ peptide by up‐regulation of metalloproteases, which are mainly implicated in the degradation of Aβ peptide . A report revealed that bis(thiosemicarbazonato)copper complex, Cu(II)‐gtsm enhances neurite elongation and neuritogenesis in neuronal cells .…”
Section: Introductionmentioning
confidence: 99%